1990
DOI: 10.1016/0014-5793(90)80782-e
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP activates receptor‐operated cation channels in mouse lacrimal acinar cells to promote calcium influx in the absence of phosphoinositide metabolism

Abstract: In exocrine acinar cells a variety of neurotransmitters (e.g. acetylcholine) stimulate phosphatidyhnositol4,5-bisphosphate hydrolysis elevating intracellular calcium to activate calcium-dependent membrane currents (outward K+ and inward Cl-). This study shows that in lacrimal acinar cells extracellular application of ATP is also associated with outward and inward current responses; these, however, are not the result of phosphoinositide metabolism. ATP directly activates receptor-operated cation channels which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
63
3
3

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 17 publications
2
63
3
3
Order By: Relevance
“…Reverse transcriptase polymerase chain reaction (RT-PCR) analysis on single acini from the rat pancreas revealed that they contain transcripts for P2X 1 , P2X 4 , P2Y 2 and P2Y 4 receptors [77]. Interestingly, no transcript for P2X 7 receptors was found, although these receptors are expressed in ducts (see below) and also in acini of other exocrine glands [78][79][80][81]. Clearly, P2X 7 receptors, which can form lytic pores under some conditions, would be dangerous in pancreatic acini filled with digestive enzymes.…”
Section: Pancreatic Acinimentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse transcriptase polymerase chain reaction (RT-PCR) analysis on single acini from the rat pancreas revealed that they contain transcripts for P2X 1 , P2X 4 , P2Y 2 and P2Y 4 receptors [77]. Interestingly, no transcript for P2X 7 receptors was found, although these receptors are expressed in ducts (see below) and also in acini of other exocrine glands [78][79][80][81]. Clearly, P2X 7 receptors, which can form lytic pores under some conditions, would be dangerous in pancreatic acini filled with digestive enzymes.…”
Section: Pancreatic Acinimentioning
confidence: 99%
“…In comparison, about 90% of acini prepared from other exocrine glands (e.g. salivary and lachrymal glands) using similar methods respond to ATP, although there is a functional heterogeneity in P2X 4 , P2Y 2 and P2Y 1 receptors, and these acini also express P2X 7 receptors [78,79,81,[83][84][85][86][87][88]. It is also established in exocrine gland acini that distribution and function of some P2 receptor is influenced by the developmental state, innervation and duration of cell culture [78,[87][88][89][90].…”
Section: Pancreatic Acinimentioning
confidence: 99%
“…Позаклітинний АТР спричинює збільшення цитозольної концентрації Са 2+ в екзокринних ацинарних клітинах різних залоз, взаємодіючи з Р2-типом пуринорецепторів [33][34][35]. Із цієї групи, в базальній мембрані ацинарних клітин сльозових залоз мишей, екс пресуються Р2Y 11 і Р2Y 13 -рецептори [36].…”
unclassified
“…Examples include receptor-gated channels (12), channels activated by second messengers such as cyclic nucleotides (13), phosphatidylinositol 3,4,5-trisphosphate (14), and arachidonic acid (15,16) (for a review see Refs. 17 and 18).…”
mentioning
confidence: 99%